Adaptive management in wildlife conservation - and Organ, John; Decker, D.J.; McDonald, J.E.; Riley, Shawn; Mahoney, S.P. (The Wildlife Society Techniques Manual, 2012)
Adaptive management in wildlife conservation emerged from the wildlife profession's search for better solutions to increasingly complex conservation challenges. Adaptive management is an effective process for wildlife managers to employ to (1) deal with uncertainty in the management system, (2) learn from their management actions, and (3) achieve desired results. Being adaptable or flexible in your management approach is not the same as managing adaptively or conducting adaptive management. Adaptive management requires adhering to a stepwise process and fully executing each step. A critical step is rigorous monitoring and assessment of management interventions. Without this, wildlife managers cannot achieve the essence of adaptive management, which is the explicit goal of learning more about the management system after each management action.